Projecting the effects of climate change on Calanus finmarchicus distribution within the U.S. Northeast Continental Shelf - Brian D. Grieve (Nature Portfolio, 2017)
Abstract Calanus finmarchicus is vital to pelagic ecosystems in the North Atlantic Ocean. Previous studies suggest the species is vulnerable to the effects of global warming, particularly on the Northeast U.S. Shelf, which is in the southern portion of its range. In this study, we evaluate an ensemble of six different downscaled climate models and a high-resolution global climate model, and create a generalized additive model (GAM) to examine how future changes in temperature and salinity could affect the distribution and density of C. finmarchicus. By 2081–2100, we project average C. finmarchicus density will decrease by as much as 50% under a high greenhouse gas emissions scenario. These decreases are particularly pronounced in the spring and summer in the Gulf of Maine and Georges Bank. When compared to a high-resolution global climate model, the ensemble showed a more uniform change throughout the Northeast U.S. Shelf, while the high-resolution model showed larger decreases in the Northeast Channel, Shelf Break, and Central Gulf of Maine. C. finmarchicus is an important link between primary production and higher trophic levels, and the decrease projected here could be detrimental to the North Atlantic Right Whale and a host of important fishery species.